Monitoring and Control Food Temperature and Humidity using Internet of Things Based-on Microcontroller - Riadi, Imam; Syaefudin, Rizal (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2021)
Tempe is a traditional Indonesian food that uses tempeh mushrooms (Rhizopuz Oryzae) to make it. Tempeh fungus on soybeans requires a certain temperature and humidity in order to grow properly. In this study, a tool was built to monitor and control temperature and humidity with an online system using the ESP8266 WiFi Module with the ESP8266-01 series, which then the data will be sent to Thingspeak and Thingsview. The method used in this study through several stages, including Hardware Design, Internet of Things (IoT) Design or Network Architecture, Testing, and Measuring temperature and humidity values. The hardware design includes Microcontroller-based system hardware to help control temperature and humidity. IoT design or network architecture steps to make connections between hardware and software, while the last stage is testing and measuring the temperature and humidity values to determine the accuracy of the system being made. The Temperature and Humidity settings are carried out automatically using the Arduino Board to control Heater and Fan. The average temperature and humidity values generated in the measurement were 33.11 C and 87.74%. This tool has a measurement accuracy compared to other measuring instruments with a standard deviation of temperature error of 0.8708 and humidity 1.1254 for 180 data samples for 3 days. In this study, the system functions properly with the control system functioning properly, and the reading of the value produces a good standard deviation.